2005
DOI: 10.1007/s11373-004-8172-x
|View full text |Cite
|
Sign up to set email alerts
|

The distinct effects of a butanol fraction of Bidens pilosa plant extract on the development of Th1-mediated diabetes and Th2-mediated airway inflammation in mice

Abstract: Bidens pilosa is claimed to be useful for immune or anti-inflammatory disorders; however, little scientific evidence has been published concerning its function. In this paper, immune disease mouse models were used to study the function of a butanol fraction of B.pilosa. We demonstrated treatment with the butanol fraction of B.pilosa ameliorated Th1 cell-mediated autoimmune diabetes in nonobese diabetic (NOD) mice but caused deterioration of Th2 cell-mediated airway inflammation induced by ovalbumin (OVA) in BA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 36 publications
1
27
1
1
Order By: Relevance
“…We corroborate that these extracts do not show a relevant antileishmanial activity. On the other hand, an essential oil extracted from Ocimum sanctum showed in vitro activity against Leishmania donovani (Zheljazkov et al, 2008) and curcumin, the active principle of Curcuma longa, was capable of blocking the action of both nitric oxide and nitric oxide congeners on the Leishmania parasite (Chang et al, 2005). However, we did not observe a relevant antileishmanial activity with these extracts tested in our study.…”
Section: Plants Speciescontrasting
confidence: 88%
See 1 more Smart Citation
“…We corroborate that these extracts do not show a relevant antileishmanial activity. On the other hand, an essential oil extracted from Ocimum sanctum showed in vitro activity against Leishmania donovani (Zheljazkov et al, 2008) and curcumin, the active principle of Curcuma longa, was capable of blocking the action of both nitric oxide and nitric oxide congeners on the Leishmania parasite (Chang et al, 2005). However, we did not observe a relevant antileishmanial activity with these extracts tested in our study.…”
Section: Plants Speciescontrasting
confidence: 88%
“…The ethanol extract was proven to be active against Plasmodium falciparum drug-resistant parasites in vitro and in rodent malaria in vivo (Andrade-Neto et al, 2004), which constitutes a previous demonstration of its antiparasitic action. However, this plant is claimed to be useful for immune or anti-inflammatory disorders, specifically inhibiting TH1 cell differentiation (Chang et al, 2005). This immunomodulatory action will be negative to leishmaniasis control, as Leishmania is an intracellular obligate parasite, and the induction of TH1 response from mammalian host is needed to protect against infection (Alexander & Russell, 1992).…”
Section: Plants Speciesmentioning
confidence: 99%
“…An Asteraceae plant, Bidens pilosa, has been used to treat diabetes in Brazil, Mexico, and Taiwan (28 -31). Other and we have shown that two polyacetylenic compounds from this plant prevented and treated type 1 and type 2 diabetes (32)(33)(34). In this study, we show that another polyacetylene from B. pilosa, cytopiloyne, effectively prevents the development of type 1 diabetes in NOD mice and determine its likely mechanism of action.…”
mentioning
confidence: 52%
“…This implies the mechanism by which cytopiloyne can prevent the onset of non-obese diabetes. (Chang et al, 2005). Therefore, the bioactive fraction of Bidens pilosa containing polyacetylenic glucosides might risk aggravating allergy and asthma though this fraction and its derived polyacetylenes have a beneficial effect on Th1 cell-mediated autoimmune diseases such as diabetes.…”
Section: Discussionmentioning
confidence: 99%